2017
DOI: 10.1177/0767370117738707
|View full text |Cite
|
Sign up to set email alerts
|

Le rôle des imaginaires dans la construction d’un marché innovant : une étude ethnomarketing du marché des nanotechnologies

Abstract: L’objectif de cet article est de comprendre dans quelle mesure les imaginaires peuvent jouer un rôle dans la construction d’un marché innovant. Nous avons mené une étude ethnomarketing du processus de construction du marché des nanotechnologies et, à cette occasion, analysé les stratégies de trois catégories d’acteurs : les consommateurs, les objecteurs et les promoteurs. Les résultats révèlent une nouvelle forme de construction des marchés : la construction symbolique. Elle repose, dans le cas des nanotechnol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 68 publications
0
8
0
6
Order By: Relevance
“…Certains piliers peuvent être privilégiés au dépend d’autres, à l’exemple de Humphreys et Latour (2013) pour qui les entreprises illégitimes agissent particulièrement sur les structures cognitives des populations afin de légitimer leur existence et leurs pratiques. Au sein de ces dimensions, les mécanismes peuvent être plus ou moins explicites (Humphreys, 2010a) en faisant référence à des scripts culturels auxquels les individus sont attachés ou à des imaginaires symboliques valorisant certains marchés (Bellion et Demontrond, 2018).…”
Section: Revue De La Littératureunclassified
“…Certains piliers peuvent être privilégiés au dépend d’autres, à l’exemple de Humphreys et Latour (2013) pour qui les entreprises illégitimes agissent particulièrement sur les structures cognitives des populations afin de légitimer leur existence et leurs pratiques. Au sein de ces dimensions, les mécanismes peuvent être plus ou moins explicites (Humphreys, 2010a) en faisant référence à des scripts culturels auxquels les individus sont attachés ou à des imaginaires symboliques valorisant certains marchés (Bellion et Demontrond, 2018).…”
Section: Revue De La Littératureunclassified
“…Some pillars may outweigh others, as found by Humphreys and Latour (2013) who found that illegitimate companies preferentially act on cognitive structures at the population level to legitimize their place and their practices. Within these dimensions, the mechanisms can work on a gradient of explicitness (Humphreys, 2010b) by referencing cultural scripts that people are attached to or symbolic imaginaries that attach value to certain markets (Bellion and Robert-Demontrond, 2018).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…She flags the difference between substance and rhetoric in the strategies that these actors co-negotiated to progressively move American society towards an acceptance of casinos. Bellion and Robert-Demontrond (2018) factor in several types of actors – from the media to consumers and back to design engineers, industries and even artists, in their paper on how the nanotechnologies market emerged. Although Munir and Phillips (2005) focused on Kodak, they also spotlighted the counter-moves of Kodak’s competitors in the process of legitimizing photography as an activity for the masses.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations